Co-Existence Of The Old And New Models Of The World Legal Order Of Territoriality: Where Does The Primacy Lie? - Sharma, Surya P. (Journal of Malaysian and Comparative Law, 1991)
The Cold War is over, political, economic, religious and cultural barriers that used to divide nations and peoples are gradually breaking, and the international community is getting pretty close to the final step leading to an interdependent or "one world". Could it, consequently, be claimed that the state-oriented Westphalian international state system stands abandoned or national sovereignties are totally lost so that from now on there will be no disputes concerning territories: and boundaries between nations? This paper is purported to demonstrate that despite the current integrationist tendencies, the old territorial order based on state sovereignty is just about as firm as it ever was (although some structural alterations are needed) and that disputes concerning territories or boundaries are going to stay on, with fluctuating intensity and alarm though.